A Cation-Chloride Cotransporter Gene Is Required for Cell Elongation and Osmoregulation in Rice . Issue 1 (16th March 2016) - Chen, Zhi Chang; Yamaji, Naoki; Fujii-Kashino, Miho; Ma, Jian Feng
Abstract : OsCCC1 functions as a K +, Na +, and Cl − cotransporter in rice to maintain osmotic potential for cell elongation through increasing internal solute concentrations. Abstract: Rice ( Oryza sativa ) is characterized by having fibrous root systems; however, the molecular mechanisms underlying the root development are not fully understood. Here, we isolated a rice mutant with short roots and found that the mutant had a decreased cell size of the roots and shoots compared with wild-type rice. Map-based cloning combined with whole-genome sequencing revealed that a single nucleotide mutation occurred in a gene, which encodes a putative cation-chloride cotransporter (OsCCC1). Introduction of OsCCC1 cDNA into the mutant rescued the mutant growth, indicating that growth defects of both the roots and shoots are caused by loss of function of OsCCC1. Physiological analysis showed that the mutant had a lower concentration of Cl − and K + and lower osmolality in the root cell sap than the wild type at all KCl supply conditions tested; however, the mutant only showed a lower Na + concentration at high external Na + . Expression of OsCCC1 in yeast increased accumulation of K +, Na +, and Cl − . The expression of OsCCC1 was found in both the roots and shoots, although higher expression was found in the root tips. Furthermore, the expression in the roots did not respond to different Na +, K +, and Cl − supply. OsCCC1 was expressed in all cells of the roots, leaf, and basal node. Immunoblot analysis revealed that OsCCC1 was mainly localized to the plasma membrane. These results suggest that OsCCC1 is involved in the cell elongation by regulating ion (Cl −, K +, and Na + ) homeostasis to maintain cellular osmotic potential.